Goldenhar syndrome - Hossain, Sanwar; Shahid, Zakia Sultana; Guda, Titus Leonard; Chowdhury, Forhad; Hossain, Md Somir (Anwer Khan Modern Medical College Journal, 2021)
Goldenhar Syndrome or Oculoauriculovertebral Syndrome is a complex syndrome characterized by an association of maxillomandibular hypoplasia, deformity of the ear, ocular dermoid and vertebral anomalies and the most severe form of hemifacial microsomia. Here we describe a 12 years female patient with Goldenhar Syndrome came to Ophthalmology department at Anwer Khan Modern Medical College & Hospital. AKMMC J 2022; 13(1) : 60-64